2018
DOI: 10.1080/10937404.2018.1557576
|View full text |Cite
|
Sign up to set email alerts
|

Health effects associated with occupational exposure to hand-arm or whole body vibration

Abstract: Workers in a number of different occupational sectors are exposed to workplace vibration on a daily basis. This exposure can come through use of powered-hand tools or hand-transmitted vibration (HTV). Workers can also be exposed to whole body vibration (WBV) by driving delivery vehicles, earth moving equipment, or through the use of tools that generate vibration at low dominant frequencies and high amplitudes, such as jack hammers. Occupational exposure to vibration has been associated with an increased risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 175 publications
(264 reference statements)
1
60
0
6
Order By: Relevance
“…The 6th survey on European working conditions showed that, in 2015 20 percent of employees were exposed to vibration during work. According to Krajnak (2018), workers of transportation, agriculture, construction, and manufacturing industries are exposed to Whole-Body Vibration (WBV) on a daily basis. Krajnak (2018) explains that WBV is associated with various adverse health conditions from fatigue, motion sickness and headaches, to musculoskeletal disorders, digestive issues, neuropathies, cardiovascular disease, type II diabetes, and potentially cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The 6th survey on European working conditions showed that, in 2015 20 percent of employees were exposed to vibration during work. According to Krajnak (2018), workers of transportation, agriculture, construction, and manufacturing industries are exposed to Whole-Body Vibration (WBV) on a daily basis. Krajnak (2018) explains that WBV is associated with various adverse health conditions from fatigue, motion sickness and headaches, to musculoskeletal disorders, digestive issues, neuropathies, cardiovascular disease, type II diabetes, and potentially cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic adverse effects that result from local hand-arm vibration may include a cardiovascular response (echocardiographic changes (an increase in ejection fraction and stroke volume, enlarged left ventricular diastolic dimension, and reduction in heart rate) and lower blood pressure) [ 38 ], immunological changes (e.g., an increase in T cell lymphocytes of CD4 and CD8), and suppression of serum total cholesterol and triglyceride levels [ 36 , 37 , 38 ]. Vibration may promote vascular injury, endothelial injury, microvasculature changes [ 39 , 40 , 41 ], defects in vascular repair, and intravascular abnormalities (release of vasoactive mediators) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pored mokroklime, kao najčešći faktori neadekvatnih uslova rada u procesima industrijske proizvodnje, kao i njihov uticaj na zaposlene, izdvajaja se izloženost visokim nivoima buke [20][21][22][23][24], vibracijama [25] i ergonomskim rizicima [26,27], kao i nesreć ama koje uključuju korišćenje mašina i opreme za rad. Negativni uticaj hemijskih supstanci na zdravstveno stanje zaposlenih žena, koje su prisustne u sve većim količinama u procesu proizvodnje i obrade tkanina, iz godine u godinu se povećava, što se može uvideti iz sprovedenih studija brojnih autora [28][29][30][31][32].…”
Section: Uvodunclassified